The Effect of Leadership Compensation and Work Discipline on Employee Performance (Study at PT Panca Putra Solusindo Jakarta) - Aryanti, Ita; Perkasa, Didin Hikmah (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This study aims to determine the effect of compensation, leadership and work discipline on employee performance at PT Panca Putra Solusindo. This type of research uses causal quantitative methods to determine the effect of variable x on variable y. The population in this study were employees of PT Panca Putra Solusindo, namely as many as 50 employees. The sample for this research was 50 employees using the saturated sample method, where all employees were sampled. The data analysis technique in this study used Partial Least Square (PLS) SEM. The first stage was to create a research instrument for distributing questionnaires and processing data. The second stage examines the effect of each variable of compensation, leadership and work discipline on employee performance and the third stage results of the research. The results of the study partially show that Leadership and Work Discipline have an effect on Employee Performance, while Compensation has no effect on Employee Performance at PT Panca Putra Solusindo